Analisis Kesalahan Menyusun Kalimat Tanya Bahasa Jerman - Fajri, Surya Nurul; R, Mantasiah; Saud, Syukur (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This research is a qualitative descriptive study aimed at identifying the forms of errors in constructing German interrogative sentences and the factors that cause students of class XI IPS 7 at SMAN 15 Makassar to make these errors. The data in this study consists of the results of a test on constructing German interrogative sentences and a questionnaire on the factors contributing to errors in forming such sentences. The data sources were obtained from the German interrogative sentence construction test completed by 35 students of class XI IPS 7 at SMAN 15 Makassar. These students were selected based on an interview with the German teacher, who stated that many students in this class were prone to making errors in constructing interrogative sentences. Based on the research instruments and data collection techniques, this study used tests and questionnaires to obtain research data. The results of the error analysis in constructing German interrogative sentences revealed three (3) forms of errors, totaling 411 instances (65.23%). These errors consist of verb conjugation errors (200 instances, 48.6%), subject placement errors (191 instances, 46.4%), and interrogative word placement errors (20 instances, 5.0%). Errors in constructing German interrogative sentences among all students were most commonly found in questions using the interrogative word was, with a total of 81 errors (19.71%). The overall percentage of errors in constructing German interrogative sentences among class XI IPS 7 students at SMAN 15 Makassar was 65.23%, which falls into the "very high" category. The factors contributing to students' errors in constructing German interrogative sentences consist of two aspects: internal and external factors. The questionnaire analysis showed that the most dominant factor was the internal factor, specifically the lack of understanding of German interrogative sentences, with a relative frequency of 80%. Meanwhile, the external factor was the influence of the mother tongue, with a relative frequency of 42.86%. Thus, efforts are needed to reduce these two contributing factors in order to minimize errors in constructing German interrogative sentencesKeywords: Error analysis, constructing, interrogative sentences, German language